Effect of Gum Chewing on Duration of Postoperative Ileus after C-Section - ZOHRA KHANUM SABA KHALID MUHAMMAD ARS, RIZWANA ANJUM, (Journal of Fatima Jinnah Medical University, 2018)
Summary: Postoperative ileus is very common after abdominal operations, like C-section. Pain, stress of surgery, immobilization and bowel paralysis all contribute to this delay. Prolonged delay in ileus can lead to lengthen stay in hospital, low immunity, hospital acquired infections and complications. C-section, regarded as low risk procedure, is most frequently performing major operation being highest therefore, even miner improvement in caesarean care might have important social and economical benefits. Objective: The objective was to compare the outcome in patients with C-section with and without gum chewing in immediate postoperative period. Study design: Randomized control trial. Settings: This study was conducted in the Obstetrics and Gynaecology, department, Lady Aitchison Hospital, Lahore. Method: This study was completed from 01-12-2011 to 31-05-2012, 70 cases were selected (35 in each group). Sample technique was purposive non-probability sample. Results: The mean age of patients of group A (Study group) was 29.06±2.37 years while of group B (Control group) mean age was 28.23±1.92. The mean gestational age of patients in group A was 37.74±0.61 weeks while in group B mean gestational age was 37.94±0.68. In group A, the mean time interval to passage of flatus for first time was 19.82±1.33 while 27.04±0.91 hours in group B which is statistically significant (p 0.40). The mean time to first post operative defecation 23.72±1.13 hours in group A while 33.11±1.81 hours in group B; p=0.038), which is statistically significant. The mean & standard deviation was 2.96±0.23 for group A and 3.06±0.48 days for group B which shows statistically significant difference (p=<0.001). Conclusion: In study group A there were shorter time of first passage of flatus, less time of first defecation and shorter hospital stay of patients.